Impactos da duplicação de rodovias : variação da mortalidade de fauna na BR 101 Sul - Dornelles, Sidnei da Silva (Universidade Federal de São Carlos, 2015)
Roadkill and isolation of populations due to the barrier effect can be considered the main direct impacts of roads on wildlife. Mammals by behavioral, size and charisma features are one of the groups of vertebrates that require mitigation for mortality, as they are also among the most seriously injured on roads. An important approach to effectively mitigate roadkill on highways is to locate the points where roadkill are concentrated. The objective of this study was to evaluate the variation in mortality of mammals due to the duplication of the BR 101 highway south. In addition to the K Ripley aggregation analysis, were generated habitat suitability models (MAH) to identify favorable locations roadkill species, using the model functional groups for prediction of highway stretches with more chances to roadkill. It was recorded 21 taxa of mammals get hit, being the most abundant gender Didelphis (n = 721), followed by Cerdocyon thous (n = 108). The abundance of carcasses decreases between before and after the duplication (F 18.04 p = <0.001). Hotspots were not overlapped between the periods analyzed, indicating that some explanatory factor has changed over the work. Observing the variables that contributed most to the models for each functional group, we noted that there were differences in the most influential variables for each functional group in different periods. Of the nine generated models, we note that six variables contributed more than 20% in different models. There were differences between the periods before, during and after the duplication of the variables that contributed most or contribution value in functional groups. These differences may reflect the change in the distribution of roadkill among highway doubling periods. Both approaches demonstrated that there have been changes in the magnitude and distribution of roadkill in the period prior to the period after duplication. So a highway with two paviments differ from a highway with four paviments about how the mammals react in terms of movement and relationship to landscape.
Keywords: Ecologia; Ecologia de estradas; Atropelamento; Modelos de adequabilidade de habitat; Duplicação de rodovias; Road ecology; Roadkill; Habitat suitability models; Highway duplication; CIENCIAS BIOLOGICAS::ECOLOGIA